The three paradoxes of the energy transition - Assessing sustainability of large-scale solar photovoltaic through multi-level and multi-scalar perspective in Rwanda. (15th March 2021) - Brunet, Carole; Savadogo, Oumarou; Baptiste, Pierre; Bouchard, Michel A.; Cholez, Céline; Gendron, Corinne; Merveille, Nicolas
Abstract: Among renewable energies, photovoltaic solar energy has a prominent place with a 25% increase in installed capacity worldwide in 2018, including the development of grid-connected photovoltaic solar power plants. These new technological tools promise to supply populations with clean energy and to fight climate change by reducing CO2 emissions, in perspective with sustainable development. Basing on a qualitative case study located in Rwanda, this article draws from the impacts of a photovoltaic solar power plant by concretely verifying to what extent its impact (evaluated in seven categories on four territorial levels) actually participates in this sustainability strategy. The article engages in an analytical discussion on the place of the solar power plant in a socio-technical Multi-Level Perspective, enriched with a Multi-Scalar approach. The study reveals three major paradoxes: (i) at the international level, the promotion of the energy transition to renewable energies (symbolized by the power plant) does not lead to systematic local electrification; (ii) although the operation of the power plant generates carbon credits from the Credit Carbon Mechanism, it does not necessarily ensure the implementation of local socio-economic development and yet this development is in principle linked to the allocation of the said credits; and (iii) due to its indirect impact on the electricity tariff, the power plant seems to limit the State's actions with regards to the fight against poverty, which seems contradictory to the impetus aroused by the new renewable energy economy. Appropriate recommendations have been proposed. Highlights: Solar power plant can generate positive impacts with appropriate local strategy. Multi-level and scalar analysis needed to assess energy transition sustainability. Energy transition does not necessarily go with better local electrification. Carbon credits can be attributed without ensuring community development. Financing green transition could jeopardize poverty alleviation.